2006
DOI: 10.1002/eji.200535593
|View full text |Cite
|
Sign up to set email alerts
|

R‐form LPS, the master key to the activation ofTLR4/MD‐2‐positive cells

Abstract: Lipopolysaccharide (endotoxin, LPS) is a major recognition marker for the detection of gram-negative bacteria by the host and a powerful initiator of the inflammatory response to infection. Using S-and R-form LPS from wild-type and R-mutants of Salmonella and E. coli, we show that R-form LPS readily activates mouse cells expressing the signaling receptor Toll-like receptor 4/myeloid differentiation protein 2 (TLR4/MD-2), while the S-form requires further the help of the LPS-binding proteins CD14 and LBP, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
176
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 74 publications
6
176
0
1
Order By: Relevance
“…Two types of biologically active LPS are synthetized by Gram-negative bacteria, smooth (S) and rough (R) form LPS (S-LPS and R-LPS). LPS-binding proteins (LBP) and CD14 are required for the activation of cells by S-LPS via the TLR4/ myeloid differentiation factor-2 receptor complex, whereas R-LPS activates various target cells including BMMs in the absence of these proteins (18,19). In agreement, we found that the TNF-α response to S-LPS in MPI cells, AMs, and BMMs is highly dependent on LBP and CD14 (Fig.…”
Section: Mpi Cells and Ams Require Lps-binding Protein And Cd14 To Sensesupporting
confidence: 79%
See 1 more Smart Citation
“…Two types of biologically active LPS are synthetized by Gram-negative bacteria, smooth (S) and rough (R) form LPS (S-LPS and R-LPS). LPS-binding proteins (LBP) and CD14 are required for the activation of cells by S-LPS via the TLR4/ myeloid differentiation factor-2 receptor complex, whereas R-LPS activates various target cells including BMMs in the absence of these proteins (18,19). In agreement, we found that the TNF-α response to S-LPS in MPI cells, AMs, and BMMs is highly dependent on LBP and CD14 (Fig.…”
Section: Mpi Cells and Ams Require Lps-binding Protein And Cd14 To Sensesupporting
confidence: 79%
“…According to the current consensus, LBP/CD14 help is required for S-LPSbut not R-LPS-triggered cell activation (18,19,31). Therefore, our present finding suggests the existence of an alternative, cell type-specific activation mechanism in MPI cells and AMs.…”
Section: Discussionsupporting
confidence: 61%
“…In several experiments, the results obtained with commercial LPS were compared with highly purified LPS from Salmonella abortus equi, kindly donated by Dr. C. Galanos (Max Planck Institute, Freiburg, Germany) [70]. No differences were found.…”
Section: Reagentsmentioning
confidence: 99%
“…Recently, it has been shown that the rough (R)-form LPS can interact with TLR4 without CD14 (12,13). Re-form LPS (lipid A + two 3-deoxy-D-manno-2-octurosonic acid residues), but not the smooth (S)-form LPS, can induce tumor necrosis factor-alpha (TNF-α) responses also in the absence of CD14 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Re-form LPS (lipid A + two 3-deoxy-D-manno-2-octurosonic acid residues), but not the smooth (S)-form LPS, can induce tumor necrosis factor-alpha (TNF-α) responses also in the absence of CD14 (12). R-form LPS was a potent activator of mast cells (that lack CD14), while S-form LPS was practically devoid of stimulatory activity (13). Since human neutrophils either lack or express low amounts of mCD14, it became important to study if LPS-induced neutrophil activation is different when stimulated by S-or R-form LPS.…”
Section: Introductionmentioning
confidence: 99%